DESAIN KOMUNIKASI VISUAL DAN PERILAKU KONSUMEN - Limandoko, Bagus (Institute of Research and Community Outreach - Petra Christian University, 2000)
The word design is a word with different meanings. In the visual communication context it has became part of the team in the communication industry - the world of advertising%2C magazine and newspaper publishing%2C marketing and public relations%2C and%2C indeed%2C it has became one of the influential aspects to shape the behavior of a society and its economic development. Abstract in Bahasa Indonesia : Desain merupakan sebuah kata dengan banyak makna. Dalam konteks komunikasi visual%2C desain sudah menjadi bagian dari tim dalam industri komunikasi. Dunia advertising%2C publikasi majalah dan suratkabar%2C pemasaran dan public relations%2C dan yang pasti desain juga sudah menjadi salah satu aspek yang berpengaruh dalam membentuk perilaku suatu masyarakat dan perkembangan ekonominya. design%2C designer%2C visual communication design%2C behavior%2C consumer